Biodiversity and resilience interventions: Analysis of interviews with farmers in the United States - Kuncz, Adina; Castellano, Michael; Zhang, Wei (International Food Policy Research Institute, 2022)
This note summarizes the results of in-person interviews with 16 US farmers in Iowa and Illinois to identi-fy the motivations and challenges that impact farmers’ adoption of practices that improve biodiversity. The respondents—mostly considered relatively progressive farmers—were identified through the Illinois Soil and Water Conservation District and the farmer network of the team leader based at Iowa State University, and thus were not representative. These interviews are part of the Enhancing Biodiversity and Resilience in Crop Production project, which was commissioned by Bayer and implemented in col-laboration with ETH Zurich and IFPRI. The project analyzed information that can contribute to guidance on using agricultural practices to improve biodiversity and resilience of farming systems. It focused on intensive maize, wheat, and soy production systems in France, Germany, Brazil, and the United States.